Les stéréotypes culturels dans Une année chez les Français de Fouad Laroui - Kulagina, Olga (Romanica Silesiana, 2021)
This paper deals with the linguistic representation of cultural stereotypes that greatly influence the interaction of French and Moroccan cultures in the novel A Year with the French (2010) by Fouad Laroui, a Moroccan-Dutch French-language writer, as the multicultural and autobiographical character of his work makes this text a particularly interesting and credible study material. We are going to put under analysis the linguistic means used to translate the stereotyped view of each culture by the other and the representation of autostereotypes and heterostereotypes. Finally, we will define the impact of these stereotypes on the communicative behaviour of the representatives of the two cultures in question, in particular their way of either becoming more enclosed in their own identity or, on the contrary, of overcoming differences and finding common ground.